Achievement of full enteral feeding using volume advancement in infants with birth weight 1,000 to <2,000 grams - Teti Hendrayanti; Afifa Ramadanti; Indrayady Indrayady; Raden Muhammad Indra (Indonesian Pediatric Society Publishing House, 2020)
Background Early enteral feeding is one of the efforts to improve gastrointestinal adaptability in preterm infants. Volume advancement (VA) enteral feeding has been associated with less time to reach full feeding, which can improve outcomes. Objective To evaluate the duration of VA needed to achieve full enteral feeding (FEF) in low birth weight (LBW) and very low birth weight (VLBW) infants and related factors. Methods This prospective study was done in infants with birth weight 1,000 to <2,000 grams in the Neonatal Ward and NICU of Dr. Moh. Hoesin General Hospital, Palembang, South Sumatera. All infants underwent VA feeding. The time needed to achieve FEF (150 ml/kg/day) was recorded. Several clinical factors were analyzed for possible associations with the success rate of achieving FEF within 10 days of feeding. Results Thirty-five infants were included in this study with a mean gestational age of 31.83 (SD 2.67) weeks.  Their median body weight at the start of protocol was 1,400 (range 1,000 - 1,950) grams and 80% had hyaline membrane disease. Median time to achieve FEF was 11 (range 8-21) days, with 48.6% subjects achieving FEF in ≤10 days. Gestational age <32 weeks (OR 5.404, 95%CI 0.963 to 30.341), birth weight <1,500 grams (OR 5.248, 95%CI 0.983 to 28.003), and male (OR 4.751, 95%CI 0.854 to 26.437) gender were associated with the failure of achieving FEF within 10 days of feeding, however, no factors remained statistically significant after multivariate analysis. Conclusion Full enteral feedings in infants with birth weight 1,000 to <2,000 grams with VA feeding are achieved within a median of 11 days. Gestational age, birth weight, and gender are not associated with time needed to achieve FEF.